Ten new aurovertins from cultures of the basidiomycete Albatrellus confluens - Guo, Hua (Springer Berlin Heidelberg, 2013)
Aurovertins J-S (1–10), together with four known metabolites, aurovertins B, C, E, and I (11–14), were isolated from cultures of the basidiomycete Albatrellus confluens. The structures of compounds 1–10 were elucidated on the basis of extensive spectroscopic analysis. All compounds were evaluated for their cytotoxic activities on five tumor cell lines. [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s13659-012-0088-y and is accessible for authorized users.